การศึกษาปัจจัยที่มีผลต่อภาวะความเครียดของพนักงานต้อนรับส่วนหน้าของโรงแรม ในเขตเมืองพัทยา จังหวัดชลบุรี The Study of factors affecting work-stress among hotel front office staff in Pataya, Chonburi Province - สุดาบุตร สุดารัตน์; กวงเพ้ง ศิริวรรณ; โพชารี ลินจง (Chophayom Journal, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์ศึกษาปัจจัยที่มีผลต่อภาวะความเครียดในการทำงานของพนักงานต้อนรับส่วนหน้าของ โรงแรม ในเขตเมืองพัทยา ชลบุรี โดยใช้แบบสอบถามเป็นเครื่องมือในการเก็บรวบรวมข้อมูลจากพนักงานต้อนรับส่วนหน้าในโรงแรมระดับ 3-5 ดาวในเขตเมืองพัทยา จังหวัดชลบุรี จำนวน 234 คน สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน t-test และ F-test (ANOVA) ผลการวิจัยพบว่า พนักงานต้อนรับส่วนหน้า ยอมรับว่าในการทำงานแต่ละวันมีภาวะเครียดปานกลาง ซึ่งปัจจัยที่มีผลต่อภาวะความเครียดเกิดจากหลากหลายปัจจัยแต่ ปัจจัยที่มีผลต่อความเครียดมากที่สุด คือ ด้านครอบครัว การวิจัยครั้งนี้ยังพบว่าความแตกต่างที่เกี่ยวข้องปัจจัยส่วนบุคลได้แก่ เพศ อายุ ประสบการณ์การทำงาน และระดับมาตรฐานโรงแรมมีอิทธิพลต่อระดับภาวะความเครียดของพนักงานแต่ละคนอีกด้วย คำสำคัญ: ความเครียด, พนักงานต้อนรับส่วนหน้า, ธุรกิจโรงแรม Abstract The aims of the research were to study investigated factors affecting job stress of hotel staff. Specifically, the study sought to identify factors affecting job stress among front office staff of 3 – 5 star hotels in Pataya of Chonburi Province, one of the well-known tourism destinations in Thailand. The study collected relevant data by using questionnaire survey. The questionnaires were distributed to front office staff of 3-5 star hotels in Pataya. There were 234 questionnaires returned and used for the data analysis. The analysis reveals that the front office staff agreed that there were a number of factors affecting their job stress. However, family factor was seen to have significant impact on their behavior at work. This research also found that the different related personal factors, including gender, age, work experience and hotel star standard has an influence on the stress level of the employee. Keywords: Stress, Front Office Staff, Hotel Business